Effects of ultrasonic energy on the wash fastness of reactive dyes - KOÇAK, EMİNE DİLARA; USTA, İSMAİL (ELSEVIER SCIENCE BV, 2004)
The field of ultrasonic is still making strides towards perfection, but already many applications of ultrasonic energy have been found in science and technology. There is also a field called sonochemistry where ultrasonic energy is used to create some chemical and mechanical effects on matter immersed or solved in liquids. It was presumed that ultrasonic textile washing could be a competitive alternative to conventional textile washing techniques; and as such the following experiments were conducted. In this study, the effects of ultrasonic energy on the wash fastness of reactive dyes, which have three different reactive groups, were investigated. After dyeing with the conventional method, the samples were applied with three types of washing processes simultaneously (conventional, ultrasonic probe and ultrasonic bath) and comparisons were made. Three different fixing agents were used in the washing processes. Colourfastness, staining fastness, magnitude of total colour difference (DeltaE) and lightness difference of the colour (DeltaL) values of dyed samples were measured. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: ultrasonic energy; wash fastness; reactive dyes